The reunion - Quinn, Meghan (Montlake, 2022)
When the Chance siblings, all unable to find love, reunite to plan the ultimate fiftieth anniversary party for their parents, they all must contend with romantic entanglements, sibling rivalries and the definitive end of their childhood.